Longevity and effectiveness of aluminum addition to reduce sediment phosphorus release and restore lake water quality. (15th June 2016) - Huser, Brian J.; Egemose, Sara; Harper, Harvey; Hupfer, Michael; Jensen, Henning; Pilgrim, Keith M.; Reitzel, Kasper; Rydin, Emil; Futter, Martyn
Abstract: 114 lakes treated with aluminum (Al) salts to reduce internal phosphorus (P) loading were analyzed to identify factors driving longevity of post-treatment water quality improvements. Lakes varied greatly in morphology, applied Al dose, and other factors that may have affected overall treatment effectiveness. Treatment longevity based on declines in epilimnetic total P (TP) concentration averaged 11 years for all lakes (range of 0–45 years). When longevity estimates were used for lakes with improved conditions through the end of measurements, average longevity increased to 15 years. Significant differences in treatment longevity between deeper, stratified lakes (mean 21 years) and shallow, polymictic lakes (mean 5.7 years) were detected, indicating factors related to lake morphology are important for treatment success. A decision tree developed using a partition model suggested Al dose, Osgood index (OI, a morphological index), and watershed to lake area ratio (related to hydraulic residence time, WA:LA) were the most important variables determining treatment longevity. Multiple linear regression showed that Al dose, WA:LA, and OI explained 47, 32 and 3% respectively of the variation in treatment longevity. Other variables (too data limited to include in the analysis) also appeared to be of importance, including sediment P content to Al dose ratios and the presence of benthic feeding fish in shallow, polymictic lakes. Graphical abstract: Highlights: Improvements in TP, Secchi depth, and Chl a occurred after Al treatment in most lakes. Al dose and lake hydrology and morphology were important for treatment success. Benthic feeding fish negatively affected treatment longevity in shallow lakes. Adequate monitoring programs are needed to assess treatment outcomes.